Pengendalian Persedian Bahan Baku Semen Dengan Pendekatan Just In Time (Studi Pada Perusahaan Semen PT. NHR) - Abdurrahman Faris Indriya Himawan (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Background - PT. NHR is one of the new arrivals in the world of the cement industry in Indonesia, which was founded in 2011. Increased efficiency can be done in various activities in the company, one of which is by controlling inventory properly. The method that can be used by companies to manage their inventory is the Just In Time method. Objective - This study aims to determine the factors that cause the accumulation of the main raw material for cement and to determine the implementation of Just In Time in the inventory of the main raw material for cement at PT. NHR. Design / methodology / approach - The type used is the type of qualitative research. There are 2 (two) studies, namely, key informants are the Head of the Warehouse Department, the Head of the Warehouse Operational Shift, and the Head of the Production Department. While non-key informants are Warehouse Operational Shift Staff, amounting to 3 (people). Determination of the informants was chosen by purposive sampling. Results and discussion - The results showed that the factors causing the accumulation of the main raw material for cement in PT. NHR, namely (1) Inaccurate measurement of the main raw material for cement, (2) Negligent and inaccurate workers (3) Weak visual control of workers in the field due to lack of labor, hot weather and declining health, (4) Purchase of raw materials main cement with large quantities. Conclusion - Implementation of the Just In Time system at PT. NHR has indirectly been implemented but is still not optimal because in the process of purchasing the main raw materials, cement is carried out in large quantities or not in accordance with the company's production plans.